Game Edukasi Math & Trash Berbasis Android dengan Menggunakan Scirra Construct 2 dan Adobe Phonegap - Ida Widaningrum; Hardi Prasetiyo; Indah Puji Astuti (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Educational games can be used as an effective learning method, especially for children, because children can gain knowledge in a fun way. Here the game is designed for young children to practice arithmetic and knowledge to separate organic and inorganic wastes. This game is based on Android using Construct 2 software, design using UML and Game Development Life Cycle (GDLC). At the end of the manufacturing process, software tests or tests consist of unit tests, integration tests and system tests. From the test results, the game